T85. THE EFFECT OF ADJUNCT ARIPIPRAZOLE ON MEASURES OF TOBACCO USE AND CRAVING IN WOMEN WITH PSYCHOTIC DISORDERS. (9th April 2019) - Wehring, Heidi; Powell, Megan; Sayer, Mackenzie; Hackman, Ann; Buchanan, Robert; Nichols, Rebecca; Adams, Heather; Richardson, Charles; Vyas, Gopal; McMahon, Robert; Earl, Amber; Sullivan, Kelli; et al.
Abstract: Background: Women with serious mental illnesses like bipolar disorder and schizophrenia are more likely to be tobacco smokers as compared to women without mental illness. Antipsychotic medications may impact craving and nicotine's rewarding effects via dopaminergic neurotransmitter activity. Differences in pharmacologic profiles and receptor affinity among antipsychotic agents may lead to variability in impact on craving and/or substance use. Aripiprazole, a partial dopamine agonist antipsychotic, may impact tobacco craving. To our knowledge, no one has specifically examined tobacco craving/usage patterns in women with psychotic disorders treated with adjunctive aripiprazole. Methods: We report baseline and endpoint tobacco use/craving data for cigarette smokers completing a 16-week randomized double-blind placebo-controlled trial of adjunct aripiprazole vs placebo. Participants recruited were all women with high prolactin levels and not reporting any desire to change smoking behaviors, which provides the opportunity to look at a naturalistic population. Assessments included the Fagerstrom Test for Nicotine Dependence (FTND) Scale, the Tobacco Craving Questionnaire-Short Form (TCQ-SF), the Drug and Alcohol Use Summary, expired carbon monoxide (CO), and all answered questions about smoking habits at baseline, 8 weeks, and 16 weeks (endpoint). Between-group changes from baseline to endpoint were measured by Effect size (Cohen's D) due to the underpowered pilot nature of the data. Results: Of the 16 women smokers included, 9 were assigned to aripiprazole and 7 to placebo. The average age of participants was 38.5 years (SD=9.9) and mean age at onset of illness was 20.9 (SD=8). The average number of cigarettes smoked daily was 10.6 (SD=7.6) and the average years of smoking was 20.9 (SD=10.4). Of the 16 participants, 2 (12.5%) were diagnosed with bipolar disorder, 4 (25%) had schizoaffective disorder, and 10 (62.5%) had schizophrenia. There were no baseline differences in demographic or smoking measures between groups. During the 16-week study the FTND scores were moderately decreased with aripiprazole relative to placebo with an effect size (ES) of -0.49. The ES for expired CO favoring aripiprazole was -0.86, however there wasn't a decrease in the aripiprazole group, only an increase noted in the study with placebo. Aripiprazole, compared to placebo, did not appear to affect the number of cigarettes smoked daily (ES= -0.22) or the TCQ-SF scores (ES= 0.20). Discussion: This pilot study is the first to evaluate the effect of adjunct aripiprazole on measures of tobacco and use and craving in women smokers with psychotic disorders. In this small sample there were moderate effect size favoring adjunct aripiprazole on a decrease in dependency scores but not in craving and cigarette smoking. Future research should investigate the impact of aripiprazole on tobacco craving in a larger sample. Additionally, both men and women should be included for a representative sample and to examine potential sex differences. This study was funded by NIMH R01 (MH090071-04) (Kelly PI) and NIDA K23 (DA034034-01A1) (Wehring PI). Aripiprazole and matching placebo were supplied by Bristol-Myers Squibb/Otsuka.